MATERNAL MENTAL HEALTH MODERATES THE RELATIONSHIP BETWEEN OXYTOCIN AND INTERACTIVE BEHAVIOR. Issue 4 (25th June 2015) - Samuel, Simcha; Hayton, Barbara; Gold, Ian; Feeley, Nancy; Carter, C. Sue; Zelkowitz, Phyllis
ABSTRACT Mothers with mood or anxiety disorders exhibit less optimal interactive behavior. The neuropeptide oxytocin (OT) has been linked to more optimal interactive behaviors in mothers without mental illness, and it may play a particularly beneficial role in mothers with mood or anxiety disorders given its antidepressant and anxiolytic functions. We compared the relationship between OT and interactive behavior in mothers with and without mental health problems. Participants included 20 women diagnosed with postpartum mood or anxiety disorders (clinical sample) and 90 women with low levels of depression and anxiety during pregnancy and postpartum (community sample). At 2 months' postpartum, blood was drawn to assess maternal OT levels, and mother–infant interaction was coded for maternal sensitivity, intrusiveness, remoteness, and depressiveness. Clinical mothers exhibited less sensitive, more intrusive, and more depressive interactive behaviors than did community mothers. The groups did not differ in OT levels. Mothers with higher OT levels were less intrusive with their infants. Higher OT levels were associated with less depressive interactive behavior only in clinical mothers. OT was associated with positive interactive behaviors in both groups. In clinical mothers, the calming and soothing effects of OT may promote more relaxed, energetic, and infant‐focused interactive behaviors.